Impact of dihydropyrrol derivative on the normal colonic mucosa of DMH-induced colon cancer rats compared with 5-fluorouracil - Kuznietsova, H.M.; Ogloblya, O.V.; Ryabchenko, V.K. (Experimental Oncology, 2013)
Aim: To compare the effects of cytostatic compound dihydropyrrol derivative (D1, 5-amyno-4-(1,3-benzothyazol-2-yl)-1-(3-methoxyphenyl)-1,2-dihydro-3Н-pyrrol-3-one) and 5-fluorouracil (5-FU) on the normal colonic mucosa of tumor-bearing rats and to estimate the relationships between proliferation of normal colonic mucosa and tumor growth parameters. Methods: 1,2-dimethylhydrazine (DMH) carcinogenic model was used. Male Wistar rats were treated by dimethylhydrazine (20 mg/kg of body weight (b.w.) weekly) for 20 weeks, by D1 (2.3 mg/kg of b.w. daily) for 7 or 27 weeks, and by 5-FU (45 mg/kg of b.w. weekly) for 7 weeks. The number of tumor and tumor total area in dissected colon, mitotic and crypt fission indices in surrounding colon mucosa were measured and correlations between these parameters were computed. Results: The number of tumor node and tumor total area under the influence of D1 and 5-FU were decreased by 40–54%. D1 administration has resulted in the more gentle effect on surrounding healthy colon mucosa comparing to 5-FU, particularly, on vascular bed and proliferative activity. The changes in colon mucosa proliferative activity correlate with tumor growth parameters depending on the action of D1 or 5-FU. Conclusions: D1 manifests the same antitumor activity but less toxicity comparing to 5-FU that allow to suggest its possible use as an anticancer mean. Obtained correlations could be useful for better understanding of the processes preceeding the malignant transformation and their pharmaceutical correction.